THE INFLUENCE OF PRODUCT QUALITY AND SERVICE QUALITY ON PURCHASING DECISIONS FOR SCOOPY MOTORBIKES AT ASTRA MOTOR SIDRAP - Alfina Tajuddin; Amrizal Salida; Dian Nirmasari (Universitas Ichsan Sidenreng Rappang, 2024)
This study aims to analyze and determine the effect of Product Quality and Service Quality on Purchasing Decisions for Scoopy Motorbikes at Astra Motor Sidrap. This research uses descriptive quantitative methods. The population of this study were all consumers who had purchased a scoopy motorcycle at Astra Motor Sidrap. The research sample was selected using a Nonprobability Sampling approach using the Accidental / Convenience Sampling technique so that the number of samples who became respondents was 97 people. The research data was collected using a survey method using a questionnaire and processed through the SPSS26 program to test validity and reliability, classical assumption test (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing (correlation coefficient, and coefficient of determination, t test, and F test). The results of hypothesis testing in this study indicate that partially and simultaneously product quality and service quality have a positive and significant effect on purchasing decisions for scoopy motorbikes at Astra Motor Sidrap. This illustrates that the increase in purchasing decisions by consumers is in line with the improvement in product and service quality. So that in the midst of competition and technological advances, companies are motivated to improve product quality and service quality.